2006
DOI: 10.1073/pnas.0600999103
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary diversification of cyanobacteria: Molecular–phylogenetic and paleontological perspectives

Abstract: Cyanobacteria have played a significant role in Earth history as primary producers and the ultimate source of atmospheric oxygen. To date, however, how and when the group diversified has remained unclear. Here, we combine molecular phylogenetic and paleontological studies to elucidate the pattern and timing of early cyanobacterial diversification. 16S rRNA, rbcL, and hetR genes were sequenced from 20 cyanobacterial strains distributed among 16 genera, with particular care taken to represent the known diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
330
2
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(358 citation statements)
references
References 51 publications
18
330
2
8
Order By: Relevance
“…Phormidium lucidum FACHB 238 and Spirulina platensis FACHB 882 are filamentous strains belonging to the traditional subsection III taxa that lack the capability of heterocyst formation. In 16S rDNA trees, these two strains are placed with unicellular species, indicating polyphyletic origins of filamentous morphology within cyanobacteria, as previously reported [5]. When morphological examination and the analyses of the hydrocarbon profiles were combined with the phylogenetic analysis based on 16S rDNA sequences of 20 cyanobacterial strains, we found that strains with type 1 and type 2 hydrocarbon profiles were all filamentous, whereas the strains with type 4 and type 5 hydrocarbon profiles were all unicellular.…”
Section: Analyses Of the Phylogenetic Distribution Of 16s Rdna Ado Amentioning
confidence: 57%
“…Phormidium lucidum FACHB 238 and Spirulina platensis FACHB 882 are filamentous strains belonging to the traditional subsection III taxa that lack the capability of heterocyst formation. In 16S rDNA trees, these two strains are placed with unicellular species, indicating polyphyletic origins of filamentous morphology within cyanobacteria, as previously reported [5]. When morphological examination and the analyses of the hydrocarbon profiles were combined with the phylogenetic analysis based on 16S rDNA sequences of 20 cyanobacterial strains, we found that strains with type 1 and type 2 hydrocarbon profiles were all filamentous, whereas the strains with type 4 and type 5 hydrocarbon profiles were all unicellular.…”
Section: Analyses Of the Phylogenetic Distribution Of 16s Rdna Ado Amentioning
confidence: 57%
“…The detoxification of ROS by means of enzymatic and/or non-enzymatic antioxidants like phenylpropanoids protects cell damage and minimizes the loss due to oxidative responses (Reuter et al 2010). Since these organisms are among the most primitive prokaryotes having faced several extreme environmental stresses during their evolution (Tomitani et al 2006), it is imperative to understand that their capabilities to produce antioxidative enzymes and secondary metabolites might have offered them protective strategies against abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary studies on microbes span the range of genetic diversity between the two microbial domains of life that evolved billions of years ago [1] down to genetic changes within a lineage that accumulate during the infection of a single diseased human over several weeks [2 -4]. Clearly, the predominant genetic mechanisms are likely to be distinct over the extremes of such an extensive range.…”
Section: Introductionmentioning
confidence: 99%